Overexpression of OsDof12 affects plant architecture in rice (Oryza sativa L.) - Wu, Qi; Li, Dayong; Li, Dejun; Liu, Xue; Zhao, Xianfeng; Li, Xiaobing; Li, Shigui; Zhu, Lihuang (Frontiers in Plant Science, 2015)
Dof (DNA binding with one finger) proteins, a class of plant-specific transcription factors, are involved in plant growth and developmental processes and stress responses. However, their biological functions remain to be elucidated, especially in rice (Oryza sativa L.). Previously, we have reported that OsDof12 can promote rice flowering under long-day conditions. Here, we further investigated the other important agronomical traits of the transgenic plants overexpressing OsDof12 and found that overexpressing OsDof12 could lead to reduced plant height, erected leaf, shortened leaf blade, and smaller panicle resulted from decreased primary and secondary branches number. These results implied that OsDof12 is involved in rice plant architecture formation. Furthermore, we performed a series of Brassinosteroid (BR)-responsive tests and found that overexpression of OsDof12 could also result in BR hyposensitivity. Of note, in WT plants the expression of OsDof12 was found upregulated by BR treatment while in OsDof12 overexpression plants two positive BR signaling regulators, OsBRI1 and OsBZR1, were significantly down-regulated, indicating that OsDof12 may act as a negative BR regulator in rice. Taken together, our results suggested that overexpression of OsDof12 could lead to altered plant architecture by suppressing BR signaling. Thus, OsDof12 might be used as a new potential genetic regulator for future rice molecular breeding.